If you build it, will they come? Assessing the response of tiger populations to elevated conservation efforts in lowland Nepal - Saneer Lamichhane; Abhinaya Pathak; Ajay Karki; Ambika P. Khatiwada; Chiranjibi P. Pokheral; James E. Hines; Dave P. Onorato; Taylor V. Stein; Madan K. Oli (Global Ecology and Conservation)
Thirteen countries within the distributional range of tigers adopted the St. Petersburg Declaration in 2010, committing to double their tiger populations by 2022. As a signatory to this document, Nepal elevated its tiger conservation efforts soon after the declaration was adopted. Using capture-mark-recapture (CMR) analyses of tiger survey data (2013–2022), we assessed the response of tiger populations to enhanced conservation measures in Banke and Bardia national parks (NP) in western lowland of Nepal. In Bardia NP, estimated tiger numbers increased from 49 in 2013 to 122 in 2022, and estimated population density increased from 3.39 in 2013 to 8.47 tigers/100 km2 in 2022). Female survival rate was consistently higher than male, with 87.06 % during 2013–2018 and 89.08 % during 2018–2022, compared to 72.9 % and 76.6 % for males in the respective periods. Additionally, the female population grew at a faster rate (6–7 % per year vs. ∼ 2 % per year for males). In Banke NP, tiger abundance increased from 3 to 22 between 2013 and 2022, and population density increased from 0.34 to 2.42/100 km2 over the same period. The remarkable 7-fold increase in tiger abundance within the Banke NP was facilitated by high male and female survival rates (≥ 90 % per year), as well as high recruitment rates (0.27 individual−1 year−1) from 2013 to 2018, leading to a robust (18–20 %) annual population growth rate. Tigers were recolonizing Banke NP at the beginning of this study, and the area offered ample space and a recovering prey base. This facilitated the recruitment of dispersers from the larger population in Bardia NP and allowed survival to be high by eliminating mortality due to density-dependent intra-specific aggression. Our results not only suggest that Nepal has met or exceeded its commitment to the St. Petersburg Declaration in Banke and Bardia NPs, but they highlight the ability of certain tiger populations to respond quickly and positively to enhanced conservation measures given suitable habitat and a healthy prey base.